Cardioprotection of recombinant human MG53 protein in a porcine model of ischemia and reperfusion injury. (March 2015) - Liu, Jianxun; Zhu, Hua; Zheng, Yongqiu; Xu, Zhaobin; Li, Lei; Tan, Tao; Park, Ki Ho; Hou, Jincai; Zhang, Cuixiang; Li, Dan; Li, Ran; Liu, Zhenguo; et al.
Abstract: Ischemic heart disease is a leading cause of death in human population and protection of myocardial infarction (MI) associated with ischemia–reperfusion (I/R) remains a challenge. MG53 is an essential component of the cell membrane repair machinery that protects injury to the myocardium. We investigated the therapeutic value of using the recombinant human MG53 (rhMG53) protein for treatment of MI. Using Langendorff perfusion of isolated mouse heart, we found that I/R caused injury to cardiomyocytes and release of endogenous MG53 into the extracellular solution. rhMG53 protein was applied to the perfusion solution concentrated at injury sites on cardiomyocytes to facilitate cardioprotection. With rodent models of I/R-induced MI, we established the in vivo dosing range for rhMG53 in cardioprotection. Using a porcine model of angioplasty-induced MI, the cardioprotective effect of rhMG53 was evaluated. Intravenous administration of rhMG53, either prior to or post-ischemia, reduced infarct size and troponin I release in the porcine model when examined at 24 h post-reperfusion. Echocardiogram and histological analyses revealed that the protective effects of rhMG53 observed following acute MI led to long-term improvement in cardiac structure and function in the porcine model when examined at 4 weeks post-operation. Our study supports the concept that rhMG53 could have potential therapeutic value for treatment of MI in human patients with ischemic heart diseases. Highlights: Treatment of ischemic heart disease is an unmet medical need. MG53 targets and protects injury to plasma membrane in multiple cell types. Recombinant human MG53 protein protects myocardium following I/R injury to the heart. rhMG53 might be a potential protein therapy for treatment of acute myocardial infarction.